Commenting on the Most Beautiful Names in the Qur’anic comma (The Gate of Divine Victory as a Model) (Journal of the College of Basic Education, 2022)
Every word in the Koran did not respond without the officer makes it suitable to what preceded them even closer look at the wordy too many have seen that can not be of such urgency that surroundedin minutes there fore necessitated the case that limited our search to commenting on his behalf Almighty Protagonist and his belongings in the Koran. An image the aim of God and to highlight the wisdom and consistency of the verses and well charge our subject door of victory just divine, Leaving the doors of the most beautiful names of other studies other fearing stretching and addressed in this way allow us to look in to a coherent semantic field might be called the door of victory as stand has the most beautiful names thread in the interval and tagged with verse that precede them. In my study of the names mentioned that I teach analytical by showing a relationship name wine a companion on the one hand and on the other hand, highlight the relationship of this names with the predecessor of the verse or verses to show us how wonderful and aesthetic consistencv and accuracv of expression, which was characterized by the great book of God. Van successful in this business, it is of God, and the other was stood in the effort for the benefit Muslims and God for success.